Cost-of-illness analysis reveals potential healthcare savings with reductions in type 2 diabetes and cardiovascular disease following recommended intakes of dietary fibre in Canada - Mohammad eAbdullah; Collin eGyles; Christopher eMarinangeli; Jared eCarlberg; Peter eJones (Frontiers Media S.A., 2015)
Background: Consumption of fibre-rich diets is associated with favourable impacts on type 2 diabetes (T2D) and cardiovascular disease (CVD), two of the most costly ailments worldwide, however the economic value of altered fibre intakes remains poorly understood. Methods: A cost-of-illness analysis was conducted to identify the percentage of adults expected to consume fibre-rich diets in Canada, estimate fibre intakes in relation to T2D and CVD reductions, and assess the potential annual savings in healthcare costs with reductions in rates of these two epidemics. Results: Non-trivial healthcare and related savings of CAD$35.9-$718.8 million in T2D costs and CAD$64.8-$1,295.7 million in CVD costs were calculated under a scenario where cereal fibre was used to increase current intakes of dietary fibre to the recommended levels of 38 g per day for men and 25 g per day for women. Each 1 g per day increase in fibre consumption resulted in annual CAD$2.6-$51.1 and $4.6-$92.1 million savings for T2D and CVD, respectively. Conclusions: Strategies to increase consumers' knowledge of the recommended dietary fibre intakes, as part of healthy diet, and to facilitate stakeholder synergy are warranted to enable better management of costs associated with T2D and CVD in Canada.